Heritage trail: the historical Puri Saren Agung in Bali Indonesia - Selvaraj, Bawani (Universiti Teknologi MARA, Kedah, 2025)
Ubud Palace, also known as Puri Saren Agung, is a must-see attraction in downtown Ubud. It has been home to Ubud's royal family since the late nineteenth century. This palace is currently a significant historical site in Bali, serving as a museum and cultural centre for the island's traditional arts. It was a noteworthy structure in the 1800s, when prominent Balinese painters flocked to Ubud to showcase their talents. As a result, this is one of the most ornately built structures on the island. Due to its small size, walking around the palace will take approximately 15 minutes; nonetheless, one should take their time and pay attention to the details/nuances